Presencia del oso andino Tremarctos ornatus (Carnivora: Ursidae) en el Corredor de Conservación Vilcabambaâ€“Amboró, sureste del Perú - Figueroa, Judith; Stucchi, Marcelo (THERYA, 2013)
Evaluations in situ, interviews, literature review and database of museums and zoos were performed, with the aim of identifying areas with Andean bear Tremarctos ornatus records in the Peruvian sector of Vilcabamba–Amboro Conservation Corridor. Bear presence was reported in several areas of regions Ayacucho, Junin, Cuzco, Madre de Dios and Puno, including protected areas: Ashaninka, Machiguenga and Amarakaeri Communal Reserves, Otishi, Manu and Bahuaja Sonene National Parks, Megantoni National Sanctuary, Machu Picchu Historic Sanctuary, Choquequirao Regional Conservation Area and Bosque Nublado, Pillco Grande–Bosque de Pumataki and Japu Bosque Ukumari Llaqta Private Conservation Areas. Within the corridor, the bear moves between 400 and 4,170 mas (range: 3,770 m), ranging from tropical rainforest to the highlands. The most important area for the bear, in size and variety of resources, would consist of Megantoni, Manu, Amarakaeri and Japu Bosque–Ukumari Llaqta, as it would provide a greater range of altitudes and areas in good condition. It is likely that there is connectivity between populations of Peru and Bolivia, because the records of Pampa Gloria (San Pedro de Putina Punco, Puno, Peru) are located at a distance of only 1.2 km from the Madidi National Park (Bolivia). Currently, some human activities such as forest clearing for agriculture, farming, logging, mining, oil and gas exploitation, the paving of the Inter–Oceanic Highway, among others, directly impact forest occupying by the bear, reducing the availability of important components of its habitat (food, refuge and corridors) for the maintenance of their populations. Keywords: Andean bear, environmental problematic, Peru, protected natural areas, Vilcabamba–Amboro.